Symbolic consultation and cultural simplification in the establishment of an Indonesian national park and its impacts on local livelihoods - Meilani, Mei; Andayani, Wahyu; Faida, Lies Rahayu Wijayanti; Susanti, Fitria Dewi; Myers, Rodd; Maryudi, Ahmad (Forest and Society, 2021)
This paper analyzes the processes by which the Sebangau National Park in Central Kalimantan (Indonesia) was established, along with the management activities implemented and the impacts of such activities on local communities. Employing an environmental justice lens, which revolved around procedural, recognition, and distribution issues, we found that local communities were not adequately consulted or involved in the establishment and management of the national park. Furthermore, approaches to mitigate the adverse impacts failed to fully consider the diverse cultures and customs with different livelihood strategies surrounding the park. The research also found that the options made available for local livelihoods were limited and did not meet specific needs and demands of certain ethnic groups. Overall, the transformation of the Sebangau production forest into a conservation area significantly disrupted local livelihoods and led to pronounced adverse economic, social, and cultural impacts. Thus, adequate attention to environmental justice must be made if park authorities are to improve the social acceptability of the national park. They should meaningfully engage the local communities in decision-making procedures related to park management, because they are directly impacted by the park. The authorities should also understand the different sociocultural aspects related to the local people surrounding the park and their different needs and livelihood strategies. Finally, the livelihood alternatives should be carefully assessed, and locals should be adequately consulted to ensure that these are socially and culturally accepted.